Il naufragio del visibile: l'apocalisse in Cuore di vetro di Werner Herzog (Mantichora. Italian Journal of Performance Studies, 2020)
My paper aims to analyze the attempts of cinema to represent the register of impossible and unimaginable of apocalypse through the movie Heart of Glass of Werner Herzog. The German filmmaker is well-known for his skills to turn something that is impossible to see, such as apocalypse, into visibility. In Heart of Glass Herzog uses a lot of uncanny ways of seeing, especially hypnosis, and different levels of visions, such as prophecies, ecstatic dreams, tableaux vivants of Friedrich and Brueghel’s paintings, to recreate the experience of seeing apocalypse. In this way apocalypse become a cultural device wherein the gaze faces with the mystery of the images.